Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the equation that models the linear relationship between [tex]\( x \)[/tex] and [tex]\( y \)[/tex] in the given table, we will follow these steps:
1. Identify and calculate the slope [tex]\( m \)[/tex] of the linear relationship.
2. Determine the y-intercept [tex]\( b \)[/tex].
3. Formulate the equation in slope-intercept form [tex]\( y = mx + b \)[/tex].
4. Convert the slope-intercept form to the standard form [tex]\( Ax + By + C = 0 \)[/tex].
5. Compare the result with the given options.
### Step 1: Calculate the Slope [tex]\( m \)[/tex]
Given the points (2, 6) and (4, 9) from the table, we can calculate the slope [tex]\( m \)[/tex] using the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Substituting the values, we get:
[tex]\[ m = \frac{9 - 6}{4 - 2} = \frac{3}{2} = 1.5 \][/tex]
### Step 2: Determine the Y-intercept [tex]\( b \)[/tex]
Using the slope [tex]\( m \)[/tex] and one of the points, let's use point (2, 6), we can find the y-intercept [tex]\( b \)[/tex] using the formula:
[tex]\[ y = mx + b \][/tex]
Substitute the point (2, 6) and the slope [tex]\( m = 1.5 \)[/tex]:
[tex]\[ 6 = 1.5 \times 2 + b \][/tex]
[tex]\[ 6 = 3 + b \][/tex]
[tex]\[ b = 6 - 3 \][/tex]
[tex]\[ b = 3 \][/tex]
### Step 3: Formulate the Equation in Slope-Intercept Form
Now we have the slope [tex]\( m = 1.5 \)[/tex] and the y-intercept [tex]\( b = 3 \)[/tex]. The equation in slope-intercept form [tex]\( y = mx + b \)[/tex] is:
[tex]\[ y = 1.5x + 3 \][/tex]
### Step 4: Convert to Standard Form
To convert [tex]\( y = 1.5x + 3 \)[/tex] into the standard form [tex]\( Ax + By + C = 0 \)[/tex], we need to eliminate the fraction. Multiply the entire equation by 2:
[tex]\[ 2y = 3x + 6 \][/tex]
Rearrange terms to match the standard form:
[tex]\[ 3x - 2y = -6 \][/tex]
### Step 5: Compare with the Given Options
Finally, we compare our derived equation [tex]\( 3x - 2y = -6 \)[/tex] with the given multiple-choice options:
- A: [tex]\( 2x - 3y = 6 \)[/tex]
- B: [tex]\( 2x + 3y = 6 \)[/tex]
- C: [tex]\( 2x - 3y = -6 \)[/tex]
- D: [tex]\( 3x - 2y = -6 \)[/tex]
The correct choice that matches our equation is:
[tex]\[ \boxed{D} \][/tex]
1. Identify and calculate the slope [tex]\( m \)[/tex] of the linear relationship.
2. Determine the y-intercept [tex]\( b \)[/tex].
3. Formulate the equation in slope-intercept form [tex]\( y = mx + b \)[/tex].
4. Convert the slope-intercept form to the standard form [tex]\( Ax + By + C = 0 \)[/tex].
5. Compare the result with the given options.
### Step 1: Calculate the Slope [tex]\( m \)[/tex]
Given the points (2, 6) and (4, 9) from the table, we can calculate the slope [tex]\( m \)[/tex] using the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Substituting the values, we get:
[tex]\[ m = \frac{9 - 6}{4 - 2} = \frac{3}{2} = 1.5 \][/tex]
### Step 2: Determine the Y-intercept [tex]\( b \)[/tex]
Using the slope [tex]\( m \)[/tex] and one of the points, let's use point (2, 6), we can find the y-intercept [tex]\( b \)[/tex] using the formula:
[tex]\[ y = mx + b \][/tex]
Substitute the point (2, 6) and the slope [tex]\( m = 1.5 \)[/tex]:
[tex]\[ 6 = 1.5 \times 2 + b \][/tex]
[tex]\[ 6 = 3 + b \][/tex]
[tex]\[ b = 6 - 3 \][/tex]
[tex]\[ b = 3 \][/tex]
### Step 3: Formulate the Equation in Slope-Intercept Form
Now we have the slope [tex]\( m = 1.5 \)[/tex] and the y-intercept [tex]\( b = 3 \)[/tex]. The equation in slope-intercept form [tex]\( y = mx + b \)[/tex] is:
[tex]\[ y = 1.5x + 3 \][/tex]
### Step 4: Convert to Standard Form
To convert [tex]\( y = 1.5x + 3 \)[/tex] into the standard form [tex]\( Ax + By + C = 0 \)[/tex], we need to eliminate the fraction. Multiply the entire equation by 2:
[tex]\[ 2y = 3x + 6 \][/tex]
Rearrange terms to match the standard form:
[tex]\[ 3x - 2y = -6 \][/tex]
### Step 5: Compare with the Given Options
Finally, we compare our derived equation [tex]\( 3x - 2y = -6 \)[/tex] with the given multiple-choice options:
- A: [tex]\( 2x - 3y = 6 \)[/tex]
- B: [tex]\( 2x + 3y = 6 \)[/tex]
- C: [tex]\( 2x - 3y = -6 \)[/tex]
- D: [tex]\( 3x - 2y = -6 \)[/tex]
The correct choice that matches our equation is:
[tex]\[ \boxed{D} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.